Dietary intake of zinc and iron within the female population of two farming villages in the Red River Delta, Vietnam - Samuelsson, Anna; Sjödin, Renée (SLU/Dept. of Food Science, 2012)
In many developing countries, among them Vietnam, contamination of agricultural land is a major issue that has public health implications. A fast growing population, rapid urbanization and industrialization have led to air and water emissions of potentially toxic elements (PTEs), such as cadmium (Cd). Earlier studies have shown that individuals with low iron (Fe) and zinc (Zn) status absorb larger quantities of Cd than those of adequate nutritional status. The purpose of this study was to investigate and compare the Fe and Zn intake from the foods consumed by women (15-45 years) in selected households in two agricultural villag-es in the Red River delta in Vietnam. In one of the villages the residents were involved in metal (mainly Fe) recycling activity, whereas in the other village the residents had agricul-tural production as main source of income. Interviews, followed by food intake calcula-tions, were performed. In total, 59 women were interviewed about their food intake as well as their knowledge about anemia, and the prevalence of this disease. The Zn and Fe intake values were compared to the nutrition recommendations for these elements. In the iron recycling village, the Zn intake was 12.7 mg/day/person and the Fe intake was 11.8 mg/day/person, based on the food intake a typical day. In the reference village, the Zn intake was 15.4 mg/day/person and the Fe intake was 13.2 mg/day/person. Based on a Food Frequency Questionnaire (FFQ), in the iron recycling village the Zn intake was 11.8 mg/day/person and the Fe intake was 11.1 mg/day/person, while in the reference village, the Zn intake was 12.1 mg/day/person and the Fe intake was 13.0 mg/day/person. The reasons for these differences between the villages are difficult to establish, but may be due to different eating habits regarding amounts and choice of food. When comparing the Zn intake with the nutrition recommendations from the Vietnamese National Institute of Nutrition (NIN), as well as World Health Organization (WHO) and Food and Agriculture Organization (FAO), the Zn intake is higher than the recommendations. However, the Fe intake in both villages did not reach the Fe recommendations, regardless if comparing with the recommendations from NIN or WHO. For this reason, the women in this study may be more prone to absorb Cd. In the iron recycling village, 93 % had knowledge about anemia and 14 % was suffering from it. In the reference village, the proportions are 100 % and 32 % respectively. The Zn content is high in for instance beef, clams and cheese, and the Zn need for the women in this study is fulfilled. There are different strategies to improve the Fe status of Vietnamese women. Apart from increasing the intake, through certain foods rich in Fe, the status can be improved by eating foods that enhance absorption and avoid or lower the intake of foods that inhibit absorption. Information from the National Institute of Nutrition and medical stations is another important factor when improving the health status.